2007
DOI: 10.1007/bf03191002
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of huperzine A following oral administration to human volunteers

Abstract: The objective of the present study was to investigate the in vivo pharmacokinetics of huperzine A in healthy human volunteers. Twelve subjects (M 6, F 6; age ranged from 20-25 years) participated in the study. Huperzine A was administered in tablet form at a single dose of 0.4 mg. Following oral administration, the presence of huperzine A started to appear in the plasma at 5-10 min, and reached the peak concentrations with a Cmax of 2.59 +/- 0.37 ng/ml at 58.33 +/- 3.89 min (time to reach peak level, Tmax. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Comparing with previous studies on pharmacokinetic behaviors of huperzine A in human plasma [15,17], the results from the present study suggested that transdermal administration resulted in much longer T max , lower C max , and produced a relatively constant plasma concentration, demonstrating more favorable clinic pharmacokinetic characteristics for AD treatment. Besides, no noticeable AEs were observed during the whole experiment, further manifesting the advantages of transdermal delivery.…”
Section: Pharmacokinetics Study Resultssupporting
confidence: 51%
“…Comparing with previous studies on pharmacokinetic behaviors of huperzine A in human plasma [15,17], the results from the present study suggested that transdermal administration resulted in much longer T max , lower C max , and produced a relatively constant plasma concentration, demonstrating more favorable clinic pharmacokinetic characteristics for AD treatment. Besides, no noticeable AEs were observed during the whole experiment, further manifesting the advantages of transdermal delivery.…”
Section: Pharmacokinetics Study Resultssupporting
confidence: 51%
“…Compared with the same type of drugs approved by the United States Food and Drug Administration, the unique chemical structure of Huperzine A facilitates its penetration of the blood-brain barrier. Huperzine A tends to target the frontal and temporal lobes, as well as the hippocampus of the brain [8]. It selectively inhibits acetylcholinesterase activity and thus facilitates increase in acetylcholine levels in the brain thereby improving memory and learning abilities.…”
Section: Discussionmentioning
confidence: 99%
“…Although some pharmacokinetic studies concerning huperzine A in young healthy subjects have been reported [8][9][10][11] , there are still no reports on the pharmacokinetic study of huperzine A in elderly subjects. Our preliminary experiments with huperzine A in elderly people showed that drug exposure AUC increased by 75% compared with that in young healthy individuals [8,9] .…”
Section: Discussionmentioning
confidence: 99%
“…Our preliminary experiments with huperzine A in elderly people showed that drug exposure AUC increased by 75% compared with that in young healthy individuals [8,9] . One factor may be the degraded physiological functions in elderly people compared with young people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation